Digital nudging and the perception on accuracy and sharing behaviours of local Singaporean news - Pang, Claire Qing Hui (Nanyang Technological University, 2023)
The advent of social networking sites (SNSs) has exacerbated the ongoing problem of online fake news susceptibility and sharing. Digital nudges, such as the accuracy endorsement nudge and the presentation nudge, have been proposed as plausible solutions. However, there is a dearth of research examining fake news in Singapore and nudging in the online misinformation context. The present study attempted to investigate the state of online misinformation in Singapore, and the effects of nudging on news sharing and discernment. Participants were asked to report their familiarity, sharing intention and perceived accuracy of 12 news headlines comprising 6 real and 6 fake news. 6 headlines (3 real news and 3 fake news) were evaluated in the absence of a nudge, and the other six (3 real news and 3 fake news) were evaluated in the presence of one of the following: accuracy endorsement nudge, presentation nudge, or a combination of both nudges. Our findings showed that Singaporeans were more familiar with real news than fake news. However, all three nudging conditions were ineffective in improving sharing intention and discernment of news, and the combination nudge was not more effective than single nudges. While familiarity of news headlines did not have significant effects on the effectiveness of the nudges, baseline news sharing behaviours were significantly correlated with overall sharing intentions of news headlines. Possible explanations for observed results, limitations, practical implications, and future directions are discussed.